Uso do pó da palha de carnaúba em compósitos de quitosana - Marques, Jéssica Souza (2012)
In this work a biodegradable composite using the carnauba straw s powder as reinforcement on chitosan matrix polymeric were manufactured. Firstly, were carried out the chemistry characterization of the carnauba straw s powder before and after treatments with NaOH and hexane. Goering and Van Soest method (1970), flotation test, moisture absorption, FTIR, TG/DTG, DSC and SEM have also being carried out. Composites were developed with variations in granulometry and in powder concentrations. They were characterized by TG/DTG, SEM and mechanicals properties. The results of chemical composition showed that the carnauba straw s powder is composed of 41% of cellulose; 28,9% of hemicellulose and 14% of lignin.The flotation test have indicated that the chemical treatment with NaOH decreased the powder s hidrophilicity.The thermal analysis showed increased of thermal stability of material after treatments. The results of FTIR and SEM revealed the removal of soluble materials from the powder (hemicelluloses and lignin), the material became rougher and clean. The composites obtained showed that the mechanicals properties of the composites were decreased in respect at chitosan films, and the composites with the powder at 150 Mesh showed less variation in the modulus values. The speed test of 10 mm/min showed the better reproducibility of the results and is in agreement to the standard ASTM D638. The SEM analysis of fracture showed the low adhesion between the fiber/matrix. The increase of volume of powder in the composite caused a decrease in values of stress and strain for the samples with untreated powder and treated with hexane. The composite with 50% of the powder s treated in NaOH didn t have significant variation in the values of stress and strain as compared with the composites with 10% of the powder, showing that the increase in the volume of fiber didn t affect the stress and strain of the composite. Thereby, it is concluded that the manufacture of polymeric composites of chitosan using carnauba straw s powder can be done, without need for pre-treatment of reinforcement, become the couple of carnauba straw s powder-chitosan a good alternative for biodegradable composites